Nature of electronic states at the Fermi level of metallic beta-PbO2 revealed by hard x-ray photoemission spectroscopy - Payne, D; Egdell, R; Paolicelli, G; Offi, F; Panaccione, G; Lacovig, P; Monaco, G; Vanko, G; Walsh, A; Watson, G; Guo, J; Beamson, G; et al. (American Physical Society, 2007)
The nature of electronic states at the Fermi energy in metallic β-PbO2 has been identified by hard x-ray photoemission spectroscopy (HXPS) combined with x-ray emission spectroscopy and density-functional theory calculations. Pb 6s states are strongly enhanced in HXP spectra, allowing us to locate the Fermi level above the top of the valence band. The occupied conduction-band states have significant Pb 6s character, although the major 6s contribution to the density of states is found 9 eV below the Fermi energy. The enormous potential of HXPS for the study of s states in oxides is emphasized.